The promise and challenge of virtual gaming technologies for chronic pain: the case of graded exposure for low back pain. (May 2015) - Trost, Zina; Zielke, Marjorie; Guck, Adam; Nowlin, Liza; Zakhidov, Djanhangir; France, Christopher R; Keefe, Francis
SUMMARY : Virtual reality (VR) technologies have been successfully applied to acute pain interventions and recent reviews have suggested their potential utility in chronic pain. The current review highlights the specific relevance of VR interactive gaming technologies for pain-specific intervention, including their current use across a variety of physical conditions. Using the example of graded-exposure treatment for pain-related fear and disability in chronic low back pain, we discuss ways that VR gaming can be harnessed to optimize existing chronic pain therapies and examine the potential limitations of traditional VR interfaces in the context of chronic pain. We conclude by discussing directions for future research on VR-mediated applications in chronic pain.